Environmental analysis of the alluvium of 2015 throughout the ravine Rayo de Sol, Chosica, Lima, Peru - Malca-Casavilca, Nora (2019)
The objective of this work was to perform an analysis on the influence of a natural event (alluvium) of March 2015 in the Rayo de Sol ravine. To carry out the analysis in the area, cameras were used to record the damage from the basin goes down to the upper basin of the Rayo de Sol ravine; a GPS etrex Garmin; a tape measure. The technique used was direct observation in the field by walking. It was verified that the eight dispersers were completely destroyed by the alluvium, the houses on both sides of the riverbed suffered considerable damage, as well as the structure of basic services; the scarcity presence or lack of native vegetation along the area is evident due to the anthropogenic activity, and urban solid waste layers were evidenced in both channels of the stream. The ignorance of the inhabitants about the danger of the area where they decided to locate their houses as well as the exceptional rainfall and bad practices in relation to urban development have caused the environment to be affected in both biotic and abiotic components.